The nationalization of politics : the formation of national electorates and party systems in Western Europe / Daniele Caramani. - Caramani, Daniele, 1968- (Cambridge studies in comparative politics, 2004)
Describes the transformation of politics from a territorial voting behavior to one of national homogeneity.